The effects of long-term molybdenum exposure in drinking water on molybdenum metabolism and production performance of beef cattle consuming a high forage diet - Thorndyke, Meghan, author; Engle, Terry, advisor; Ahola, Jason, committee member; Edwards-Callaway, Lily, committee member; Holt, Timothy, committee member (Colorado State University. Libraries, 2024)
In the current series of experiments the influence of long term molybdenum (Mo) exposure in the feed or water on copper (Cu) status, metabolic, reproductive, and carcass characteristics was investigated. The objective of experiment 1 was to conduct a life-cycle production and health assessment of lactating and gestating beef cattle, and their calves, exposed to varying doses of Mo. In this experiment Commercial, multiparous beef cows (n=54 in year 1; n= 51 in year 2) with calves (approximately 2 months of age) were used to evaluate the effects of Mo source (feed or water) on reproduction, mineral status, and performance in cows and calves receiving a grass hay diet [dry matter (DM) basis: 6.6% crude protein; 0.15% S, 6.7 mg Cu/kg, 2.4 mg Mo/kg] for 553 d. Cows were stratified by age, body weight (BW), and liver Cu and Mo status, and were then randomly assigned to one of six treatment groups. Treatments were: 1) Negative control (NC; basal diet with no supplemental Mo or Cu); 2) Positive control (PC: NC + Cu; 3 mg of supplemental Cu/kg diet DM from CuSO4·5H2O); 3) NC + 500 µg Mo/L from Na2MoO4·2H2O supplied in drinking water (Mo 500-water); 4) NC + 1000 µg Mo/L of Na2MoO4·2H2O supplied in drinking water (Mo 1000-water); 5) NC + Mo 1000-water + 3 mg of supplemental Cu/kg diet DM from CuSO4·5H2O (Mo 1000-water+Cu); and 6) NC + 3.0 mg of supplemental Mo/kg diet DM from Na2MoO4·2H2O (3.0 Mo-diet). During the winter months, animals were housed in three replicate pens per treatment and during the summer months animals were housed in separate pastures by treatment. Animals were allowed ad libitum access to both feed and water throughout the experiment. Cows were bred via artificial insemination during the summer months of both years of the experiment and calves were weaned at approximately 6 months of age in the fall of both years. All cows and calves were weighed, bled, and feed and water intake were determined every 28d. Cattle receiving diets containing less than 10 mg Cu/kg DM total diet became Cu deficient over the course of the experiment as determined by liver and plasma Cu concentrations. However, no Mo toxicity or Cu deficiency signs (e.g., reduction in growth rates, reproductive performance, or immune function) were observed throughout the course of the experiment for any treatment. Results suggest that Mo supplemented in water or feed at concentrations used in this experiment had minimal impact on Cu status and overall animal performance. However, dietary Cu concentration below 10.0 mg Cu/kg DM total diet reduced liver and plasma Cu concentrations to values indicative of a marginal Cu deficiency in beef cows. The objective of the chapter 3 review was to examine the impact of Mo in drinking water on cattle performance and Mo and Cu metabolism. The majority of Mo research has focused on the antagonist effect of Mo, alone or in combination with elevated dietary S, on Cu absorption and metabolism in ruminants. Diets containing both >5.0 mg of Mo/kg DM and >0.33% S have been reported to reduce the Cu status in cattle and sheep. Therefore, due to the potential for inducing Cu deficiency, Mo and S concentrations in the diet should be monitored and kept within appropriate values. Elevated sulfate concentrations in drinking water can also be detrimental to livestock production, especially in ruminants. High concentrations of sulfate in water have been extensively studied in cattle because high-sulfate water induces polioencephalomalacia in ruminants. However, little research has been conducted investigating the impact of Mo in water on Cu metabolism in ruminants. Based on the limited number of published experiments, it appears that Mo in drinking water may have a lower antagonistic impact on the cu status in cattle when compared to Mo consumed in the diet. This response may be due to a certain percentage of water bypassing the rumen when consumed by ruminants. The chapter 4 experiment objective was to of this experiment was to investigate the influence of prolonged exposure to elevated Mo water concentrations on apparent absorption and retention of both Cu and Mo in pregnant multiparous beef cows. In this experiment twelve multiparous beef cows of similar BW, age, and gestational length, from a larger cow-calf study, were utilized to evaluate the effects of molybdenum (Mo) consumption method (feed or water) on apparent absorption and retention of copper (Cu) and Mo. Cows (n=54) with calves had been assigned to one of six dietary and/or water treatments (n=9 cow-calf pairs per treatment) 301 d prior to selecting a sub-group of 12 cows. Treatments consisted of: 1) negative control (control; basal diet with no supplemental Mo or Cu), 2) positive control (control + 3 mg of supplemental Cu/kg DM), 3) control + 500 µg Mo/L from Na2MoO4·2H2O supplied in drinking water, (4) control + 1000 µg Mo/L of Na2MoO4·2H2O supplied in drinking water, (5) positive control + 1000 µg Mo/L of Na2MoO4·2H2O supplied in drinking water, and (6) control + 3.0 mg of supplemental Mo/kg diet DM from Na2MoO4·2H2O. The sub-group of cows were individually fed a low quality grass hay diet with their respective treatments, n=2 cows/treatment) for 14 d. On day 15, dry matter intake (DMI) was held at 90% of the group's average intake. Total fecal and urine output were then collected for 3 d. Dry matter digestibility and water intake were similar across treatments. Copper intake and apparent absorption and retention of Cu were greater (p < 0.05) in cows receiving supplemental Cu when compared to non-Cu supplemented cows. Apparent absorption of Mo was similar across all treatments. Apparent retention of Mo was greater while apparent absorption of Cu was lesser (p < 0.05) in cows receiving 3 mg of Mo/kg dm and cows receiving 1000 µg Mo/L when compared to all other treatments. These data indicate that Mo source (feed vs water) may impact apparent absorption of Cu in cows receiving a low quality forage diet. The chapter 5 survey of central Rocky Mountain livestock producers objective was to understand the mineral consumption within the forage and water as well as Cu and Mo status of the grazing cattle. Commercial, multiparous, crossbred beef cows from 3 independent cow-calf production operations were selected to assess the molybdenum (Mo) and copper (Cu) status of cattle raised in the Rocky Mountains. Fifteen cows from each operation were selected at random, during early summer and late fall processing. At the time of cattle processing, both jugular venipuncture blood samples and liver biopsies were obtained from each cow. Furthermore, all diet components, forage, water, and supplement samples were obtained from each location. Plasma, liver, water, and feed samples were analyzed for Mo and Cu concentrations via inductively coupled plasma mass spectrometry. Feed samples were also analyzed for moisture, crude protein (CP), ash, ADF and NDF. Water samples were sent to an established laboratory for general water quality analysis. On average, in the current survey forages samples contained 55.61% DM, 8.37% CP, 34.91% ADF, and 54.98 NDF with a Cu:Mo ratio of 2.8:1. Additionally, the water quality of the samples obtained were well within the "safe and should pose no health problems" category for beef cattle. Plasma Mo concentrations of 0.22 (±0.10) mg/kg DM were considered to be elevated in 64% of all samples obtained, likely a result of the elevated Mo forage concentrations in the grazed plant material. Plasma Cu of 0.83 (±0.11) concentrations were within normal ranges for all samples obtained. Molybdenum and Cu liver concentrations of 3.74 (±1.29) and 82.54 (±22.76) respectively, were within ranges considered to be normal for beef cattle for all samples collected. Based on the results of this survey, Mo and Cu plasma and liver concentrations in Colorado cow-calf operations in the central Rocky Mountains were similar to Mo and Cu plasma and liver concentrations in Cu supplemented cows in the previously described 2-year Mo supplementation cow-calf experiment. Furthermore, these data suggest that Cu supplementation at NASEM (2016) recommended concentrations of 10 mg Cu/kg DM total diet (or greater) meets the animals dietary Cu requirement for cattle consuming forages sampled.